2010
DOI: 10.1111/j.1582-4934.2010.01177.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer chemotherapy induces cardiotoxicity by targeting cardiac stem cells

Abstract: Overwhelming data indicate that cancer survivors are at higher risk of cardiovascular diseases because chemotherapy induces cardiotoxicity. Mechanistic explanation of this phenomenon is necessary to advise the clinical practice on the prevention of cardiotoxicity in cancer patients. Here we propose that chemotherapy induces cardiotoxicity by inadvertently interrupting the homeostasis of cardiac stem cells and depleting the resident cardiac stem cells pool. As a result, the heart loses the capability of regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For example, the enhanced CNS progenitor cell death and suppression of cell division have been seen both in vitro and in vivo after chemotherapeutic treatment (Dietrich et al 2006). Also, it has been shown that cancer chemotherapy induces cardiotoxicity by targeting cardiac stem cells (Li et al 2010). Consequently, the prevention of stem cell loss during cancer treatment could be one of the desirable therapeutic tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the enhanced CNS progenitor cell death and suppression of cell division have been seen both in vitro and in vivo after chemotherapeutic treatment (Dietrich et al 2006). Also, it has been shown that cancer chemotherapy induces cardiotoxicity by targeting cardiac stem cells (Li et al 2010). Consequently, the prevention of stem cell loss during cancer treatment could be one of the desirable therapeutic tasks.…”
Section: Discussionmentioning
confidence: 99%
“…In various organs, the stem cells and cancer cells are subjected to a toxic effect of antineoplastic drugs. It is known that chemotherapy may induce apoptosis in both malignant and normal cells (Hannun 1997;Li et al 2010). Therefore, the protection of stem cells from injuries in tissues is an important therapeutical goal.…”
Section: Introductionmentioning
confidence: 99%
“…CSCs express the receptor of growth hormone releasing hormone (GHRH), and GHRH-agonist therapy substantially improved cardiac performance and reduced infarct size, partly via a regenerative process [156]. Pharmacological inhibition of Akt alleviated blockade of lineage commitment in CSCs, and cancer chemotherapy induces cardiotoxicity by targeting CSCs, further confirming pharmacological approaches as modulators of the reservoir of CSCs [89,157]. …”
Section: Strategies To Activate Cscs In Situmentioning
confidence: 99%
“…Drug effects on potassium currents could lead to QT-prolongation, potentially fatal arrhythmias and sometimes cardiomuscular damage without affecting ion channels [ 42 , 74 ]. Cancer chemotherapies might cause cardiomyocyte apoptosis and dysfunction; however, different chemotherapeutics might have different toxicity mechanisms [ 75 , 76 ]. In pharmaceutical industries, the cardiotoxicity test models are based on cell lines, animal cardiomyocytes, and small/large animal models [ 40 , 41 ].…”
Section: Esc and Ipsc-derived Cardiomyocytes In Toxicity Testingmentioning
confidence: 99%